Optimizing the Reduction of Total Suspended Solids in Pump Water from Fish Factories Through Electrocoagulation using Response Surface Methodology - Aguilar Ascón, Edwar (2021)
This study aims to optimize the removal of total suspended solids (TSS) in pump water from fish flour factories through electrocoagulation technology and to determine the effects of the main operation parameters. Pump water has high conductivity (40.1 mS), due to the presence of dissolved salts and contains high concentration of organic substances (12,360 mg/L of TSS and 520 mg/L of fats). In this study, pump water was treated in an electrocoagulation reactor with aluminum electrodes using Response Surface Methodology with a 3kfactorial design based on two factors, current intensity (I) of 8–13 A and treatment time (t) of 20–40 minutes. The percentage of TSS removed from the water was used as the response variable. The results revealed that I and t significantly (p < 0.05) influenced the process. In accordance, the optimal operational parameters for TSS removal were I = 13 A and t = 30 minutes. Using these conditions, TSS removal efficiency of 99.9% was achieved. The sewage sludge generated with these optimal process conditions indicated 19.3% of ash content, 6.2% of salt, 1.7% of aluminum, 0.3% of iron, 0.4% of potassium, 256 ppm of zinc, and 2.1% of phosphorus. Hence, the results of this study affirm that electrocoagulation can be considered as a solution for marine pollution caused by fishing industries.